The Effect of Teacher’s Work Discipline and Principal’s Academic Supervision on Teacher’s Performance - Ramlan, Yafani; Ahyani, Nur; Fitria, Happy (Journal of Social Work and Science Education, 2024)
The purpose of this study is to ascertain how teacher performance in junior high schools in Simpangkatis District, Central Bangka Regency, is influenced by teacher work discipline and school principal academic supervision. 77 instructors from junior high schools in Simpangkatis District, Central Bangka Regency, made up the sample size. Purposive sampling was used in the sampling process, with some teachers from junior high schools in Simpangkatis District, Bangka Tenga Regency, serving as the respondents. To collect data, questionnaires with a 5-point Likert scale measuring 85 statement items were distributed. Multiple linear regression analysis is the method utilized for analysis. The study’s findings indicate that teacher work behavior and the principal’s academic oversight have an impact on how well teachers perform. Second, teacher work discipline has an impact on their performance. Third, the academic oversight provided by the principal has an impact on teachers’ performance.